Joint effects of weather and interspecific competition on foraging behavior and survival of a mountain herbivore. Issue 2 (14th May 2018) - Ferretti, Francesco; Lovari, Sandro; Stephens, Philip A
Abstract: Weather variations have the potential to influence species interactions, although effects on competitive interactions between species are poorly known. Both weather and competition can influence foraging behavior and survival of herbivores during nursing/weaning, a critical period in the herbivore life cycle. We evaluated the joint effects of weather and competition with red deer Cervus elaphus on the foraging behavior of adult female Apennine chamois Rupicapra pyrenaica ornata in summer, and on winter survival of chamois kids. High temperature and low rainfall during the growing season of vegetation had negative effects on bite rate. Effects of weather were greater in forb patches, including cold-adapted, nutritious plants of key importance to chamois, than in graminoid ones. Our results confirm previous indications of a negative effect of competition on bite rate of female chamois and on kid survival. Furthermore, harsh weather conditions and competition with deer had additive, negative roles on foraging behavior and survival of chamois. Growing temperatures are expected to influence distribution, growth, and/or nutritional quality of plants; competition would reduce pasture quality and food availability through resource depletion. Both factors would limit food/energy intake rates during summer, reducing survival of the youngest cohorts in winter. We suggest that interspecific competition can be an important additive factor to the effects of weather changes on behavior and demography.